Use of a new combination of xylazine-midazolam for rats sedation - Zeni Coronel, Estefania Magali (2022)
One of the most used and routinely established anesthetic modalities in rodents, is ketamine (K) combined with benzodiazepines; however, K induces secondary undesired effects, added to that its acquisition in Argentina is difficult due to being considered an abuse drug. To avoid these adverse, bureaucratic and economic obstacles, we evaluated the possibility of replacing ketamine/xylazine (KX) by an anesthesia protocol that could provide a quick and effective surgical level of anesthesia and allow full access to the oral cavity. Wistar rats (n=24) were subject to the application of saline solution 3 times a week and weekly replacement of the periodontal ligature (PL) under a combination of 20 mg X/Kg and 5 mg midazolam (M)/Kg. After 21 days, animals were sacrificed and soft organs (liver, kidneys and duodenum) were extracted for histology and pharmacological combination safety verification. The time for sedation (in seconds) was evaluated and compared against the KX combination. Results: average ± SD (min-max): ataxia 113±60 (62-325); lateral decubitus 164±62 (76-359); foot reflex 306±112 (129-537) and ocular reflex 527±215 (145-1063). Mortality and respiratory distress were not observed. Ataxia marked the beginning of the induction period and was obtained after less than 2±1 min compared to 8.8±4.0 min with KX. After the completion of the dental procedure with XM, foot reflex recovery required 38±14 min and ocular reflex 43±19 min. Sedation lasted: 77±10min versus 20-40 min induced by intramuscular/intraperitoneal K/X (40-90 mg/kg/5-15mg/kg, respectively). Variability in depth of anesthesia was not observed in XM as compared to the marked variability observed with KX combination. Conclusion: Induction to the anesthetic plane was significantly shorter with XM than KX combination. The tested combination appears to be a suitable alternative to replace KX for minor oral procedures, as well as for longer surgical interventions due to its prolonged anesthesia effect.